The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/s1415-47572014005000001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and mapping of a spotted leaf mutant in rice (Oryza sativa)

Abstract: Spotted leaf mutant belongs to a class of mutants that can produce necrotic lesions spontaneously in plants without any attack by pathogens. These mutants have no beneficial effect on plant productivity but provide a unique opportunity to study programmed cell death in plant defense responses. A novel rice spotted leaf mutant (spl30) was isolated through low-energy heavy ion irradiation. Lesion expression was sensitive to light and humidity. The spl30 mutant caused a decrease in chlorophyll and soluble protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…PCD was also demonstrated by a DNA laddering during lesion formation (data not shown). To confirm that ROS accompanied PCD, we performed a DAB staining assay to assess H 2 O 2 accumulation, in which a reddish-brown polymer precipitate is generated by the interaction between DAB and H 2 O 2 in the presence of peroxidase [ 61 ]. After staining, a large amount of reddish-brown precipitate was only observed at necrotic sites in the lm3 mutant leaves ( Fig 4E–4H ), and dark reddish-brown staining appeared with increasing severity of necrosis ( Fig 4F and 4H ), indicating a high level of H 2 O 2 accumulation in the lm3 mutant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCD was also demonstrated by a DNA laddering during lesion formation (data not shown). To confirm that ROS accompanied PCD, we performed a DAB staining assay to assess H 2 O 2 accumulation, in which a reddish-brown polymer precipitate is generated by the interaction between DAB and H 2 O 2 in the presence of peroxidase [ 61 ]. After staining, a large amount of reddish-brown precipitate was only observed at necrotic sites in the lm3 mutant leaves ( Fig 4E–4H ), and dark reddish-brown staining appeared with increasing severity of necrosis ( Fig 4F and 4H ), indicating a high level of H 2 O 2 accumulation in the lm3 mutant.…”
Section: Resultsmentioning
confidence: 99%
“…The spl30(t) lesions were induced through light, including fluorescent light, and enhanced by higher temperatures [ 22 ], whereas the lesions of the rice Oslsd1 mutant were induced at a lower temperature and under shorter duration of daylight [ 1 ]. Moreover, the expression of lesion spots in spl30 mutants is sensitive to light and humidity [ 61 ]. In the present study, no visible lesions were detected under the 0 -h photoperiod, but lesions appeared under illumination, indicating that the mutant was light dependent, similar to the LF2010A mutant [ 14 ] and the LM lines derived from the Yanzhan1/Zaosui30 cross [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…These mutants spontaneously develop localized cell death lesions resembling those caused by HR in the absence of pathogen infection, abiotic stress or mechanical damage (Xu et al , 2014). Many LMMs display significantly enhanced resistance to disease (Wang et al , 2015 a ; Wang et al , 2015 b ) and it is believed that such mutants are ideal tools for deciphering the signal pathways of PCD and defense responses in plants.…”
Section: Introductionmentioning
confidence: 99%
“…The hypersensitive response (HR), a type of PCD, is the most common characteristic of plant disease resistance, which triggers rapid cell death to inhibit further invasion of pathogens in host plant tissues [ 3 ]. Lesion mimic mutants (LMMs) or the specifically termed spotted-leaf (spl) mutants in rice could produce necrotic lesions similar to that caused by HR without pathogen infection, abiotic stress or mechanical damage [ 4 ]. In fact, it has been reported that numerous rice spl mutants display significantly enhanced disease resistance to multiple pathogens [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%